Vehicle and Automotive Engineering Proceedings of the JK2016, Miskolc, Hungary - Jármai, Károly; Bolló, Betti; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents the proceedings of the first vehicle engineering and vehicle industry conference. It captures the outcome of theoretical and practical studies as well as the future development trends in a wide field of automotive research. The themes of the conference include design, manufacturing, economic and educational topics.
Design -- Manufacturing -- Economy -- Education.
Keywords: Automotive engineering; Metals; Automotive Engineering; Metals and Alloys